Nutrient Priming in Different Maize Cultivars and Evaluation of Vigour Improvement Under Controlled Conditions - Umair, Adnan; Abid, Muhammad; Ali, Ijaz; Bashir, Kashif; Naseem, Waqas; Rauf, Hafiz Abdul (Biological Sciences - PJSIR, 2017)
Laboratory and pot experiments were conducted to study the effect of seed priming on vigour and germination characteristics of different maize cultivars during the year 2011. The seeds of four maize cultivars viz. EV 7004Q, Islamabad Gold, Rakaposhi and Sohan-3 were primed using 0% P (dry seeded control), 0.6% P and 1.2% P solutions of KH2PO4 for 16 h. The experiment was laid out in Complete Randomized Design (CRD) having three replicates. All the seed priming treatments significantly improved the plant vigour in terms of enhanced germination percentage, reduced mean germination time (MGT), improved root, shoot lengths and dry matter production. Among the four cultivars of maize the Islamabad Gold performed best followed by Sohan-3. Highest germination (94.57%) and vigour index (VI) of 431.66 was observed in Islamabad Gold where 1.2% P applied compared to dry seeded control. Nutrient seed priming may be used to improve germination vigour and crop stand establishment under field conditions leading to good yield targets in maize under rainfed conditions.